2006
DOI: 10.3892/ijmm.18.5.925
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of histamine receptor subtypes in a human bronchial epithelial cell line

Abstract: Abstract. Histamine is a well-known mediator eliciting a broad range of responses in different cell types. Four different subtypes of G protein-coupled histamine receptors (H 1 -H 4 ) have been cloned and pharmacologically characterized. However, involvement of the different histamine receptor subtypes in immunomodulatory functions of bronchial epithelium has only been investigated marginally. The expression and function of histamine receptor subtypes on the human bronchial epithelial cell line BEAS-2B was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…It has been largely demonstrated that H 3 R is mostly expressed in the central and, to a lesser extent, in the peripheral nervous system. Only a small number of experimental observations have showed its presence on non-neuronal cell types such as rodent fundic mucosa endocrine cells [26], cholangiocytes [37], pancreatic β-cells [38], and in the human bronchial epithelial cell line BEAS-2B [39]. Therefore, our data add a new non-neuronal localization of the H 3 R, contributing to the hypothesis that the H 3 R could also mediate nonneuronal histamine effects.…”
Section: Discussionmentioning
confidence: 68%
“…It has been largely demonstrated that H 3 R is mostly expressed in the central and, to a lesser extent, in the peripheral nervous system. Only a small number of experimental observations have showed its presence on non-neuronal cell types such as rodent fundic mucosa endocrine cells [26], cholangiocytes [37], pancreatic β-cells [38], and in the human bronchial epithelial cell line BEAS-2B [39]. Therefore, our data add a new non-neuronal localization of the H 3 R, contributing to the hypothesis that the H 3 R could also mediate nonneuronal histamine effects.…”
Section: Discussionmentioning
confidence: 68%
“…In a previous study in human dermal fibroblast cultures, H 4 R expression was unaffected by histamine stimulation (33). Expression of the H 1 R, H 2 R, and H 3 R, but not H 4 R was demonstrated in the human bronchial epithelial cell line (34). All these data suggest that the H 4 R is probably not critical in the regulatory effects of histamine on fibroblast and epithelial cell activation in allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in several different cell types have demonstrated NF‐κB activation and release of cytokines elicited by histamine acting via the H 1 receptor subtype (Bruysters et al , 2004; Wu et al , 2004; Matsubara et al , 2005; Jin et al , 2006; Muller et al , 2006). However, whereas inflammation is complex and involves multiple mediators, including histamine and pro‐inflammatory cytokines, most investigations have examined the effects of histamine acting alone.…”
Section: Discussionmentioning
confidence: 99%